Strategic performance measurement systems and organisational learning - Mohamed, Rapiah; Wee, Shu Hui; Abdul Rahman, Ibrahim Kamal; Abdul Aziz, Rozainun (2010)
This paper reports the results of a study on strategic performance measurement systems (SPMS) and organisational learning.The main research question in this study is whether SPMS are able to facilitate organisational learning. The data was collected from a mail survey to top management of Malaysian listed companies.The results show that SPMS design makes a unique and significant contribution with organisational learning.